Effect of alcohol solvents on the structural, optical and electrical characteristics of pedot: pss polymer films annealed at low atmospheric pressure - Aimukhanov, A.K.; Rozhkova, X.S.; Ilyassov, B.R.; Omarbekova, G.I.; Seisembekova, T.E. (Eurasian Physical Technical Journal, 2022)
The paper presents the results of a study of the effect of alcohol solvents on the surface structure, optical and electrical characteristics of a Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate films annealed at a low atmospheric pressure of 10-3 millimeters of mercury. It has been found that the modification of the surface of a polymer film with ethyl and isopropyl alcohols leads to a change in the surface morphology, optical and electrical transport properties of the polymer. It is shown that when the Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film is modified with alcohol solvents, the absorption spectra show a decrease in the absorption of the polystyrene sulfonate aromatic fragment. It is shown that the structural features of the Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate surface morphology affect the electrical transport parameters of films, such as the resistance of the Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate film, the charge carrier transfer resistance at the Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate/electrode interface, the effective extraction rate, and the effective time of flight of charge carriers. The optimal technological parameters for the production of films have been determined, at which the electrical transport properties of Poly(3,4-ethylenedioxythiophene) polystyrene sulfonate films annealed at low atmospheric pressure increase
Keywords: PEDOT:PSS; Izopropanol; Ethanol; low atmospheric pressure; surface morphology; optical spectroscopy; impedance spectroscopy